Comparing the Quality of Direct-to-Consumer Telemedicine Dominated and Delivered by Public and Private Sector Platforms in China: Standardized Patient Study - Faying Song; Xue Gong; Yuting Yang; Rui Guo (JMIR Publications, 2024)
BackgroundTelemedicine is expanding rapidly, with public direct-to-consumer (DTC) telemedicine representing 70% of the market. A key priority is establishing clear quality distinctions between the public and private sectors. No studies have directly compared the quality of DTC telemedicine in the public and private sectors using objective evaluation methods. ObjectiveUsing a standardized patient (SP) approach, this study aimed to compare the quality of DTC telemedicine provided by China's public and private sectors. MethodsWe recruited 10 SPs presenting fixed cases (urticaria and childhood diarrhea), with 594 interactions between them and physicians. The SPs evaluated various aspects of the quality of care, effectiveness, safety, patient-centeredness (PCC), efficiency, and timeliness using the Institute of Medicine (IOM) quality framework. Ordinary least-squares (OLS) regression models with fixed effects were used for continuous variables, while logistic regression models with fixed effects were used for categorical variables. ResultsSignificant quality differences were observed between public and private DTC telemedicine. Physicians from private platforms were significantly more likely to adhere to clinical checklists (adjusted β 15.22, P<.001); provide an accurate diagnosis (adjusted odds ratio [OR] 3.85, P<.001), an appropriate prescription (adjusted OR 3.87, P<.001), and lifestyle modification advice (adjusted OR 6.82, P<.001); ensure more PCC (adjusted β 3.34, P<.001); and spend more time with SPs (adjusted β 839.70, P<.001), with more responses (adjusted β 1.33, P=.001) and more words (adjusted β 50.93, P=.009). However, SPs on private platforms waited longer for the first response (adjusted β 505.87, P=.001) and each response (adjusted β 168.33, P=.04) and paid more for the average visit (adjusted β 40.03, P<.001). ConclusionsThere is significant quality inequality in different DTC telemedicine platforms. Private physicians might provide a higher quality of service regarding effectiveness and safety, PCC, and response times and words. However, private platforms have longer wait times for their first response, as well as higher costs. Refining online reviews, establishing standardized norms and pricing, enhancing the performance evaluation mechanism for public DTC telemedicine, and imposing stricter limitations on the first response time for private physicians should be considered practical approaches to optimizing the management of DTC telemedicine.